SPECIFIC FEATURES OF MANAGEMENT TACTICS IN SEVERE CONCOMITANT INCISION WOUNDS OF THE HEART - I. M. Samokhvalov; S. A. Smirnov; S. V. Nedomolkin; S. V. Gavrilin; D. P. Meshakov; G. E. Ivanovskiy; V. V. Suvorov; B. N. Bogomolov; V. I. Badalov; V. Yu. Markevich; M. A. Vasilyev; M. V. Kaznacheev (Вестник анестезиологии и реаниматологии)
Heart wounds are fairly rare, out of all chest penetrating wounds they make 5-7%. The main causes of lethal outcomes in cardiac incision wounds are massive blood loss, a combination of acute massive blood loss and cardiac tamponade, and isolated cardiac tamponade. The juries of coronary arteries and intracardiac structures also provide an impact on the mortality level. The clinical observation described in the article demonstrates the opportunity to provide a favorable outcome of the trauma disease in the patients with severe concomitant incision wounds of head, neck, chest, abdomen, and acute massive blood loss when providing adequate intensive care and surgical treatment.